Identifikasi Sebaran Lapisan Batugamping Dengan Metode Geolistrik Tahanan Jenis di Kecamatan Sawa, Kabupaten Konawe Utara, Sulawesi Tenggara - Mochamad Mussoddaq; Hariono La Pili (OPHIOLITE: Jurnal Geologi Terapan, 2025)
Limestone is one of the most important non-metallic mineral commodities widely used in the cement, steel, fertilizer, and construction industries. North Konawe Regency, particularly in Sawa District, has significant limestone potential; however, subsurface distribution information remains limited. This study aims to identify the distribution of limestone using the 2D resistivity geoelectrical method with a Wenner–Schlumberger configuration. Measurements were conducted along four survey lines, each 290 meters in length with 10-meter electrode spacing, enabling subsurface investigation down to approximately 57 meters. The acquired data were processed using Res2Dinv software to generate 2D resistivity cross-sections, which were further integrated into a 3D model to estimate resource potential. Interpretation results indicate three main subsurface zones: an aquifer layer with low resistivity (8–33 Ωm), claystone with medium resistivity (64–344 Ωm), and a compact limestone layer characterized by high resistivity (474–14,772 Ωm). The 3D model reveals an extensive and continuous limestone distribution, with an estimated volume of 11,845,136 m³ across an area of 207,790 m². These findings demonstrate that the resistivity geoelectrical method is highly effective for limestone exploration, while also providing accurate preliminary data to support sustainable mineral resource management and utilization planning in the study area.